'Make the Most of the Situation'. Older Adults' Experiences during COVID-19: A Longitudinal, Qualitative Study. (October 2022) - Brooks, Emily; Mohammadi, Somayyeh; Mortenson, W. Ben; Backman, Catherine L.; Tsukura, Chihori; Rash, Isabelle; Chan, Janice; Miller, William C.
The COVID-19 pandemic restrictions have been associated with increased social isolation and reduced participation in older adults. This longitudinal qualitative study drew on life course theory to analyse data from a series of four sequential semi-structured interviews conducted between May 2020–February 2021 with adults aged 65+ ( n = 12) to explore older adults' experiences adjusting to the COVID-19 pandemic. We identified three themes: (1) Struggling 'You realize how much you lost' describes how older adults lost freedoms, social connections and activities; (2) Adapting 'whatever happens, happens, I'll do my best', revealing how older adults tried to maintain well-being, participation and connection; and (3) Appreciating 'enjoy what you have', exploring how older adults found pleasure and contentment. Engagement in meaningful activities and high-quality social interactions supported well-being during the COVID-19 pandemic for older adults. This finding highlights the need for policies and services to promote engagement during longstanding global crises.